2002
DOI: 10.1016/s1059-1311(02)00133-4
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics of adolescents with epilepsy in Northern Jordan

Abstract: Socio-demographic characteristics of this group of adolescents with epilepsy are compatible with the results of the work of others such as Elwes [Neurosurg Psychiatr 54 (1991) 200], in the North East of England and Hauser from the Mayo clinic in his descriptive study of the epidemiology of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
4
2
0
Order By: Relevance
“…Regarding sex, more than half of the studied patients were male and this agreed with Jhussein and Qaderi (2002) [20] in their study about socio-demographic characteristics of adolescents with epilepsy, they found that the male to female ratio was 54:47. But this result didn't agree with Mohammed (2018) [21] who stated that more than half of the study group was females.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding sex, more than half of the studied patients were male and this agreed with Jhussein and Qaderi (2002) [20] in their study about socio-demographic characteristics of adolescents with epilepsy, they found that the male to female ratio was 54:47. But this result didn't agree with Mohammed (2018) [21] who stated that more than half of the study group was females.…”
Section: Discussionsupporting
confidence: 88%
“…Participants who were unemployed as well as participants of high school or less education had significantly higher stigma and psychosocial burden scores than patients who were employed or were better educated. These results are in consistent with previous studies (Hussein, El-Qaderi, 2002; Smeets, van Lierop, Vanhoutvin, Aldenkamp, & Nijhuis, 2007). PWE encountered stigma in their daily lives and thus might lower the chance of obtaining a job.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding duration of disease, the higher percentage (42%) is for those who are suffering from the disease for period from 1-3 year. The finding is consistent with results of Hussein and EL-Qaderi, (2002) and Wagner, et al, (2012) (10,20) .…”
Section: Discussionsupporting
confidence: 92%